A systematic review of the views and experiences of subjects of community treatment orders. (May 2017) - Corring, Deborah; O'Reilly, Richard; Sommerdyck, Christina
Abstract: Objective: CTOS have been the subject of many qualitative and quantitative research studies. Both research approaches add value to our understanding of CTOs. Qualitative studies provide an understanding of CTOs and the experience of being on a CTO that quantitative studies cannot provide. Many qualitative studies that have examined the views of subjects of CTOs have been published. However, authors of these studies continue to note that views and experiences of the subjects of these orders are not well known. This paper provides the results of a systematic review of qualitative studies focused on understanding the experiences of individuals who have been the subjects of CTOs. Method: Relevant databases and grey literature were searched. To be included, a study had to have used a qualitative methodology for data collection and analysis, and focus on examining stakeholder perspectives on the lived experience of CTOs. Results: After a rigorous review of the abstracts, we identified 22 papers that met the criteria. These papers were analysed in detail in order to examine the existence of common themes. The 22 papers represented the views of 581 participants from 7 countries around the world. Ten themes were found to be common among the research findings of the 22 papers. Three themes in particular were highlighted: feelings of coercion and control, medication seen as the main reason for a CTO and that the perception of CTOs as a safety net. Findings also highlight the ambivalence that subjects of CTOs experience, the importance of the therapeutic relationship for successful engagement of the subject of the CTO and the complex role of coercion. Recommendations: We have made a number of recommendations about how clinicians might use the views of the subjects of CTOs achieve a more positive experience of a CTO.